Analisis Kompetensi Relatif PTUN dalam Sengketa Pencabutan Izin Lingkungan Hidup di Denpasar - Khaerunnisa, Talitha Najla; Sabrina, Alya Zahra (FIA Unkris Press, 2025)
This study examines the role of public participation in supervising environmental administrative decisions and how administrative courts apply the principle of relative competence in environmental permit disputes. The core issues include the restriction of community legal standing due to regulatory changes, the court’s narrow interpretation requiring actual losses as a prerequisite for standing, and procedural irregularities in issuing or revoking environmental permits. Using a normative juridical research method, this study analyzes the Denpasar Administrative Court’s decision on the Celukan Bawang Environmental Permit case along with relevant environmental law literature. The findings reveal that courts frequently reject public lawsuits by demanding proof of actual losses, preventing substantive issues such as flawed environmental impact assessments and climate-related concerns from being meaningfully assessed. Additionally, the Denpasar Administrative Court’s jurisdiction was affirmed based on the principle of relative competence in environmental permit revocation cases. This study concludes that public participation through administrative lawsuits remains essential for environmental protection and must be strengthened to ensure effective, transparent, and accountable oversight of state administrative decisions